Economic Opportunities for Women in the East Asia and Pacific region - Ellis, Amanda; Kirkwood, Daniel; Malhotra, Dhruv (World Bank, 2012)
East Asia and the Pacific is a region of dynamic growth. Women have contributed significantly to this growth and have benefited from it through active participation in the labor market. However, women are still disproportionately represented in the informal sector and in low paid work. Efforts to identify barriers to women's business and entrepreneurial activities in the region are critical not only to facilitate inclusive growth in a national context but also to counter the increasing trend of female migratory flows in the region. This report highlights' both the challenges and the economic opportunities for businesswomen in the region offers some useful potential pointers for reform.